A Newborn with a Large Umbilical Cord Pseudocyst with Hemangioma: A Case Report and Review of the Literature - İbrahim Akkoyun; Ethem Ömeroğlu; Musa Göncü; Hicran Kanat; Emel Ebru Özçimen (Medical Network, 2012)
Umbilical cord pseudocysts in a newborn are very rare. They may be associated with patent urachus and hemangioma. Generally, they are localized in a particular section of the cord. Urachal or vitelline duct cysts, teratoma, omphalocele, umbilical cord hernia and hematoma are considered in differential diagnosis. In this case report, we discussed the clinicopathological findings of a pseudocyst with hemangioma involving the entire cord in a newborn, and in particular the confusing conditions related to the excision of the umbilical cord.